FEATURES OF SKILLS IN WORKING WITH AUDIOVISUAL MEANS OF GEOGRAPHY EDUCATION AMONG SCHOOLCHILDREN TO ONESELF TYPICAL (International journal of artificial intelligence, 2026)
The formation of skills in working with audiovisual means of geography education among schoolchildren to oneself typical features and their types about word Today 's​ The purpose of the project is to develop skills in working with audiovisual means of geography education among schoolchildren . to oneself typical importance about information given .